2011
DOI: 10.1289/ehp.1002286
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of Diesel-Induced Endothelial Nitric Oxide Synthase Dysfunction in Coronary Arterioles

Abstract: Background and objectiveIncreased air pollutants correlate with increased incidence of cardiovascular disease potentially due to vascular dysfunction. We have reported that acute diesel engine exhaust (DE) exposure enhances vasoconstriction and diminishes acetylcholine (ACh)-induced dilation in coronary arteries in a nitric oxide synthase (NOS)-dependent manner. We hypothesize that acute DE inhalation leads to endothelial dysfunction by uncoupling NOS.MethodsRats inhaled fresh DE (300 μg particulate matter/m3)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
53
1
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 81 publications
(60 citation statements)
references
References 46 publications
5
53
1
1
Order By: Relevance
“…33 This mechanism of endothelial nitric oxide synthase uncoupling was already investigated in previous studies. 34,35 The plasma DEP concentration reached after the in vivo exposures is nevertheless unknown. It might be lower than those used in our in vitro experiments; indeed, in our normotensive group, the muscarinic relaxations of the aortas were not impaired after in vivo exposures.…”
Section: Discussionmentioning
confidence: 99%
“…33 This mechanism of endothelial nitric oxide synthase uncoupling was already investigated in previous studies. 34,35 The plasma DEP concentration reached after the in vivo exposures is nevertheless unknown. It might be lower than those used in our in vitro experiments; indeed, in our normotensive group, the muscarinic relaxations of the aortas were not impaired after in vivo exposures.…”
Section: Discussionmentioning
confidence: 99%
“…Lung cryostat sections were stained with the superoxide-sensitive fluorescent dye dihydroethidium (DHE) as previously described (20,95,104). Specific DHE fluorescence intensity was analyzed in the arterial wall using Image J software.…”
Section: Methodsmentioning
confidence: 99%
“…Elevated steady-state O 2 - levels in these vessels, as well as the ability of agonists to further increase these levels, is prevented by NOS inhibition with an L -arginine analog [23]. Reduced availability of tetrahydrobiopterin (BH 4 ), an essential cofactor for eNOS, is one of the primary causes of NOS uncoupling [35,36], and this has been documented at the level of the arterioles in various pathological settings [37,38,39]. In a follow-up study on mouse spinotrapezius muscle, arteriolar wall BH 4 levels were found to be almost 50% lower in animals with high salt intake than in those fed a normal diet [24].…”
Section: Animal Studiesmentioning
confidence: 99%